Pengaruh Dana Alokasi Khusus dan Kemandirian Fiskal Daerah terhadap Pertumbuhan Ekonomi di Kabupaten Aceh Barat Daya - Muliana, Muliana; Shifa, Mutiara; Fajri, Rahman (Lembaga Teewan Journal Solutions, 2026)
Regional economic growth is influenced by a combination of dynamics in the real sector and the fiscal capacity of local governments in managing budgets and resources. This study aims to analyze the impact of the disbursement of the Special Allocation Fund and regional fiscal autonomy on economic growth in Southwest Aceh Regency. This study employs a quantitative approach using secondary time-series data for the period 2011–2024 obtained from the Central Statistics Agency and the Directorate General of Fiscal Balance. The analysis was conducted using multiple linear regression following tests for stationarity and classical assumptions. The results indicate that, when analyzed individually, the disbursement of the Special Allocation Fund and local fiscal autonomy do not have a significant effect on economic growth. Simultaneously, the two variables also did not show a significant effect. These findings indicate that changes in fiscal resources have not yet had a strong short-term impact on regional economic growth. Therefore, fiscal management needs to be directed toward productive activities, economic infrastructure, and the strengthening of leading sectors in order to create a multiplier effect on the regional economy.